HUBUNGAN INDEKS MASSA TUBUH (IMT) TERHADAP PENINGKATAN KURVA LORDOSIS LUMBAL - Wati, Ketut Ayu Padma; Kinandana, Gede Parta; Adhitya, I Putu Gde Surya (PT. Kesehatan Gerak Fungsi Tubuh, 2024)
Background: Body mass index (BMI) is an indicator of health that is often used with the ratio between body weight and height. Health problems related to BMI vary widely, including bone problems such as lordosis. Lordosis is a disorder that causes an abnormally enlarged curvature of the vertebrae or spine. This study aimedto review the correlation between BMI and lumbar lordosis curve. Methods: This study used a literature review design.The articles that discusses the correlation of BMI and increase in the lumbar lordosis curve based on secondary data from published literature on Google Scholar and PubMed using the keywords body mass index, lumbar curve, and lordotic lumbar. Results: From 5 studies discussing the relationship between BMI and lumbar lordosis, it was found that all journals showed that there was a relationship between Body Mass Index and lumbar lordosis. Conclusion: Based on some of the literature that has been discussed, it could be concluded that the BMI correlated with the lumbar lordosis curve.